SiPINTAR Mobile Library Application: Perceived Usefulness and Ease of Use - Atty Sofiyanty; Rusmana, Agus; Khadijah, Ute Lies Siti (UPT Publikasi Ilmiah UNISBA, 2024)
Abstract. A smart system service called SiPINTAR is a smart service library application at Universitas Islam Bandung. This research aims to find out how SiPINTAR application is perceived by users based on the Technology Acceptance Method theory. This research employs a descriptive-qualitative research method. Data collection techniques are carried out by collecting information from several sources and then combining it with structured direct observations on the SiPINTAR application. The results of this study show that the convenience aspects of using SiPINTAR are easy to learn, easy to control, clear and easy to understand, easy to adjust, and easy to use. In addition, from the aspect of usability, it can facilitate work, speed up work, increase productivity, and enhance the effectiveness of users’ activities. This research concludes that SiPINTAR application is very easy to use by librarians and library users. It also provides benefits for users in terms of a positive assessment and fulfilling all aspects of the assessment, which makes SiPINTAR application positively accepted.